2021
DOI: 10.1002/cpp.2702
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive emotion regulation strategies and trait anger as predictors of depression severity

Abstract: Background According to empirical evidence, trait anger and emotion regulation strategies are associated with depression severity. The objective of this study was to investigate the impact of trait anger and maladaptive emotion regulation strategies in explaining the variance of depressive symptoms severity. Methods Two hundred three participants diagnosed with major depressive disorder completed measures of depression, trait anger, depressive rumination, anger rumination and experiential avoidance. Path analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…The results of the present study also suggested that higher levels of emotion regulation difficulties were related to greater anger. These results are consistent with those reported in previous studies where feelings of anger have been found to increase as difficulties in emotion regulation increase (19,20), especially those related to suppression or rumination (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study also suggested that higher levels of emotion regulation difficulties were related to greater anger. These results are consistent with those reported in previous studies where feelings of anger have been found to increase as difficulties in emotion regulation increase (19,20), especially those related to suppression or rumination (17).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, previous studies have associated anger with eating disorders. Greater symptoms of anorexia nervosa and bulimia nervosa have been reported among individuals with greater inappropriate anger ( 20 , 22 , 53 ). Furthermore, it has been found that following anger induction among patients with EDs, there was a significant increase in body size estimation ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…This disturbed processing of emotional information has also been shown after symptom remission and in heathy controls at higher risk for depression ( Leppänen, 2006 ). Abnormalities and difficulties in emotion regulation have been shown to be predictive for severity of depression symptoms ( Atherton et al, 2015 ; Crisan and Nechita, 2022 ). There is also some evidence that reduction in positive emotionality may predict poor outcome in MDD ( Morris et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%